Customer Loyalty and Switching Behavior in Banking Services: A Primary Survey of Kathmandu Valley Bank Customers - Shrestha, Ranu Maiya; Adhikari, Reena; Adhikari, Samyog (Academia Journal of Research and Innovation, 2026)
The customer loyalty and switching behavior is an important variable in the competitiveness and profitability of the banking sector and retention strategies are gaining insensitiveness in the growing competitive environment of Nepal financial services. This paper explores the customer loyalty patterns and switching behavior determinants among customers of commercial banks in Kathmandu Valley using a primary survey research in detail. Structured questionnaires and in-depth interviews were used to conduct a cross-sectional survey of 550 banking customers in 18 commercial banks to understand the drivers of loyalty, switching intentions, and behavioral patterns of various types of customers. The study used not only quantitative evaluation of indicators of loyalty but also qualitative evaluation of switching motivations, service quality perceptions and relationship aspects that impact on customer retention. Findings showed that 68 percent of customers were highly loyal and the strongest predictor of customer loyalty was service quality (b = 0.542, p < 0.001) then came trust (b = 0.387, p < 0.001) and switching costs (b = -0.298, p < 0.01). Almost a quarter of respondents (23 percent) had switching intentions, and the primary reasons were poor service quality (47 percent), high fees (32 percent), and limited digital services (28 percent). The customer tenure had good positive relationships with the loyalty (r = 0.63, p < 0.001), and the young customers (18-35 years) had a higher switching propensity compared to the older groups. The level of customer satisfaction was greater among the private banks (4.2 / 5.0) than in the case of the public banks (3.6 / 5.0), but the loyalty was similar because of relationship factors and switching costs. The results offer useful lessons to the banking institutions to work out effective retention strategies and competitive positioning strategies in the dynamic banking environment in Nepal.